The culture code : the secrets of highly successful groups - Coyle, Daniel (New York : Bantam Books, 2018)
'Daniel Coyle spent three years researching the question of what makes a successful group tick, visiting some of the world's most productive groups--including Pixar, Navy SEALs, Zappos, IDEO, and the San Antonio Spurs. Coyle discovered that high-performing groups relentlessly generate three key messages that enable them to excel: 1) Safety - we are connected. 2) Shared Risk - we are vulnerable together. 3) Purpose - we are part of the same story. Filled with first-hand reporting, fascinating science, compelling real-world stories, and leadership tools that can apply to businesses, schools, sports, families, and any kind of group, The Culture Code will revolutionize how you think about creating and sustaining successful groups.'--
Introduction: When two plus two equals ten -- Skill 1. Build safety -- The good apples -- The billion-dollar day when nothing happened -- The Christmas truce, the one-hour experiment, and the missileers -- How to build belonging -- How to design for belonging -- Ideas for action -- Skill 2. Share vulnerability -- 'Tell me what you want, and I'll help you' -- The vulnerability loop -- The super-cooperators -- How to create cooperation in small groups -- How to create cooperation with individuals -- Ideas for action -- Skill 3. Establish purpose -- Three hundred and eleven words -- The hooligans and the surgeons -- How to lead for proficiency -- How to lead for creativity -- Ideas for action -- Epilogue.
Includes bibliographical references (pages 249-259) and index.
Keywords: Teams in the workplace; Corporate culture; Leadership; SELF-HELP / Personal Growth / General; BUSINESS & ECONOMICS / Organizational Behavior